Training Needs of Community Health Workers Facing the COVID-19 Pandemic in Texas: A Cross-Sectional Study - Byrd-Williams, Courtney; Ewing, Mollie; Rosenthal, E. Lee; St. John, Julie Ann; Menking, Paige; Redondo, Floribella; Sieswerda, Stephanie (Frontiers in Public Health, 2021)
The COVID-19 pandemic has required the professional healthcare workforce not only to adjust methods of delivering care safely but also act as a trusted sources of information during a time of uncertainty and rapid research and discovery. The Community Health Worker COVID-19 Impact Survey is a cross-sectional study developed to better understand the impact of COVID-19 on this sector of the healthcare workforce, including training needs of those working through the pandemic. The survey was distributed in Texas, New Mexico, and Arizona. This study focuses on Texas, and the data presented (n = 693) is a sub-set of qualitative data from the larger survey. Results of the content analysis described in this paper are intended to inform current COVID-19-related CHW training curriculum, in addition to future infectious disease prevention and preparedness response trainings.